PENGARUH ESG DAN CSR TERHADAP KINERJA KEUANGAN - bella, Bella Sagita; Ronal Aprianto; Dian Wulan Sari; Yuli Nurhayati (Universitas Sangga Buana, 2025)
This study aims to analyze the effect of ESG (Environmental, Social, and Governance) and CSR (Corporate Social Responsibility) on financial performance, measured through Return On Asset (ROA) and Return On Equity (ROE) for companies listed on the Indonesia Stock Exchange. The sample used in this study consists of three companies that consistently implemented ESG principles from 2019 to 2023. The research method employed is quantitative, with data analysis conducted using EViews 13. The analysis results show that ESG disclosure does not have a significant effect on ROA, with a probability value of 0.2811 (greater than 0.05). On the other hand, CSR has a significant effect on ROE with a probability value of 0.0349 (less than 0.05). Further testing of the interaction between ESG and CSR indicates that both do not have a significant effect on ROA, with values of X1 at 0.1058 and X2 at 0.1977 (greater than 0.05). In conclusion, while CSR influences financial performance in terms of ROE, the disclosure of ESG and CSR together does not have a significant impact on ROA.